2014
DOI: 10.5665/sleep.3492
|View full text |Cite
|
Sign up to set email alerts
|

Increased Use-Dependent Plasticity in Chronic Insomnia

Abstract: This study provides the first evidence that patients with chronic insomnia have an increased plasticity response to physical exercise, possibly due to larger activation of glutamatergic mechanisms. This suggests a heightened state of neuroplasticity, which may reflect a form of maladaptive plasticity, similar to what has been described in dystonia patients and chronic phantom pain after amputation. These results could lead to development of novel treatments for chronic insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Recently, neuroimaging has also suggested that insomnia patients have higher excitability in the bilateral dorsolateral prefrontal cortex (DLPFC) compared with healthy individuals (Nofzinger, ). Moreover, TMS measures showed cortical hyperexcitability in the restless legs syndrome, chronic insomnia, and sleep deprived healthy individuals, but cortical hypoexcitability in the obstructive sleep apnea syndrome (Lanza et al, ; Lanza, Cantone, et al, ; Lanza, Lanuzza, et al, ; Lin et al, ; Nardone et al, ; Salas et al, ). Combined with the inhibitory effect on cortical excitability by low‐frequency stimulation, we speculated that sequential bilateral low‐frequency magnetic stimulation over DLPFC may have a significant therapeutic effect on PI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neuroimaging has also suggested that insomnia patients have higher excitability in the bilateral dorsolateral prefrontal cortex (DLPFC) compared with healthy individuals (Nofzinger, ). Moreover, TMS measures showed cortical hyperexcitability in the restless legs syndrome, chronic insomnia, and sleep deprived healthy individuals, but cortical hypoexcitability in the obstructive sleep apnea syndrome (Lanza et al, ; Lanza, Cantone, et al, ; Lanza, Lanuzza, et al, ; Lin et al, ; Nardone et al, ; Salas et al, ). Combined with the inhibitory effect on cortical excitability by low‐frequency stimulation, we speculated that sequential bilateral low‐frequency magnetic stimulation over DLPFC may have a significant therapeutic effect on PI.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent evidence has suggested that insomnia might have an impact on both night and day brain functioning, with changes in brain plasticity, assessed via transcranial magnetic stimulation (TMS), reported in patients with PI [ 23 ]. Such a broad repercussion on central nervous system dynamics might also suggest an interaction between age-related brain plasticity mechanisms [ 24 ], length of exposure to sleep deprivation, and age of insomnia onset.…”
Section: Introductionmentioning
confidence: 99%
“…The disruptions from psychosocial stressors may become stabilized in the brain through new neural pathways. 90 Thus, sleep difficulties stemming from the psychosocial experience prior to and throughout the adoption process may result in long-term sleep difficulties. Further, adopted children are at an increased risk for the development of psychopathology, which may also maintain sleep difficulties and create a vicious cycle of reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 86 As these changes occur, the ability to regulate sleep decreases, and sleep difficulties become stabilized neural pathways. 90 Further, these neurobiological changes may increase physiological arousal at bedtime. 91 As a result, the brain is increasing wakefulness instead of inducing relaxation and rest.…”
Section: The Biology Of Sleep and Adoptionmentioning
confidence: 99%